Lipophilic extractives from different morphological parts of banana plant “Dwarf Cavendish” - Oliveira, L. (2021)
The chemical composition of the dichloromethane extracts of different morphological parts of banana plant “Dwarf Cavendish”, cultivated in Madeira Island (Portugal), were studied by gas chromatography–mass spectrometry. The five different morpholog ical fractions in study have a similar qualitative chemical composition. Fatty acids and sterols are the major families present in the lipophilic extract of “Dwarf Cavendish”, representing ca. 33–66% and 12–43%, respectively, of the total amount of lipophilic components. Among all the identified compounds, campesterol, stigmasterol, sitosterol and fatty acids, such as palmitic, stearic, linoleic, linolenic, 22-hydroxydocosanoic, 24-hydroxytetracosanoic and 26-hydroxyhexacosanoic acids, were the major compo nents found in all morphological zones. Other families of compounds, such as aromatic compounds, fatty alcohols and alkanes were also identified. The high increase of some components after alkaline hydrolysis, particularly, ferulic and fatty acids, indicates the presence of a considerable fraction of such components in esterified structures.